Detection of Teschovirus type 13 from two swine herds exhibiting nervous clinical signs in growing pigs. Issue 2 (16th November 2017) - Carnero, J.; Prieto, C.; Polledo, L.; Martínez‐Lobo, F. J.
Summary: Recently, the number of clinical reports of growing pigs showing neurological signs possibly related to viral infections has increased. The objective of this report was to describe two outbreaks of an atypical condition observed in 6‐ to 7‐week‐old pigs with a morbidity of 20% and a fatality rate of 60% in two unrelated farms of the same company. During the acute phase of the disease, fever, sudden death, neurological signs, ear necrosis and occasional corneal opacity were observed. Histopathological examination revealed interstitial pneumonia, lymphoid depletion and lymphocytic vasculitis in different organs and mild polioencephalomyelitis suggesting a potential viral infection. Possible aetiologies such as exogenous intoxications, salt intoxication, mineral deficiencies/intoxications (Se, Cu, Cd and Zn), oedema disease and mycotoxicosis were ruled out through the diagnostic process. No clinically relevant bacteria could be consistently isolated from affected animals, and the presence of the common swine viruses was ruled out by PCR or RT‐PCR. Porcine Teschovirus serotype 13 was the only virus detected by RT‐PCR within central nervous system (CNS) of acutely affected pigs. This is the first description of PTV serotype 13 within the CNS of clinically affected pigs.